Building Sustainable Pavements: Investigating the Effectiveness of Recycled Tire Rubber as a Modifier in Asphalt Mixtures - Christina Plati; Brad Cliatt (Energies, 2021)
Building more sustainable pavements for the future requires knowledge of alternative and innovative materials for utilization in future road construction and maintenance activities. Being mindful of this need, the present study investigates a Reacted and Activated Rubber (RAR) compound modifier with the aim of defining an optimal RAR percentage in Asphalt Concrete (AC) mixes. It is acknowledged that when this type of modifier is incorporated within an AC mix as an alternative for the bituminous binder material, the associated economic, environmental and social benefits are significant. Simply put, the use of RAR modifiers provides the potential to utilize a waste product (rubber tires) as a more sustainable alternative to bitumen within AC mixtures. However, it seems that the information about the overall performance of AC mixes modified with RAR is currently limited. On these grounds, the present study focuses on the surface course layer and evaluates (a) achieved physical characteristics (compaction degree/voids), (b) mechanical characterization results (stiffness moduli) and (c) friction-based properties of tested mixtures incorporating varying RAR levels and different test temperatures. From the evaluation, it is concluded that for the case of the surface course mixture under investigation, the optimal percentage by weight of bitumen for inclusion of the RAR modifier is 10%.